2005
DOI: 10.1152/ajpcell.00483.2004
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol enhances heparin-binding epidermal growth factor-like growth factor production in human keratinocytes

Abstract: Heparin-binding epidermal growth factor-like growth factor (HB-EGF) enhances reepithelialization in wounds. Estrogen is known to promote cutaneous wound repair. We examined the in vitro effects of 17β-estradiol (E2) on HB-EGF production by human keratinocytes. E2 or membrane-impermeable BSA-conjugated E2 (E2-BSA) increased HB-EGF secretion, mRNA level, and promoter activity in keratinocytes. E2 or E2-BSA enhanced in vitro wound closure in keratinocytes, and the closure was suppressed by anti-HB-EGF antibody. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 76 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…In previous studies, it had been shown that adult male plasma/serum EGF level was two-fold higher than female in mice, and testosterone treatment of female mice doubled serum EGF level [29] and that EGF level in tear fluid was higher in male compared to female patients; [30] contrary to these reports, we measured serum EGF levels significantly higher in female compared to male volunteers (p ¼ 0.014). Our data regarding the higher serum EGF levels observed for females could be explained by the roles of some hormones reported previously as for progesterone up-regulating EGF expression [31] and, as for 17-beta estradiol enhancing heparin binding EGFlike growth factor production in human keratinocytes [32] and as well as with increasing EGF levels towards term. [33] Using the ELISA system we developed for measurement of hEGF, hEGF levels were below detectable limits in all plasma samples of all volunteers who participated in this study.…”
Section: Measurement Of Human Egf 55supporting
confidence: 70%
“…In previous studies, it had been shown that adult male plasma/serum EGF level was two-fold higher than female in mice, and testosterone treatment of female mice doubled serum EGF level [29] and that EGF level in tear fluid was higher in male compared to female patients; [30] contrary to these reports, we measured serum EGF levels significantly higher in female compared to male volunteers (p ¼ 0.014). Our data regarding the higher serum EGF levels observed for females could be explained by the roles of some hormones reported previously as for progesterone up-regulating EGF expression [31] and, as for 17-beta estradiol enhancing heparin binding EGFlike growth factor production in human keratinocytes [32] and as well as with increasing EGF levels towards term. [33] Using the ELISA system we developed for measurement of hEGF, hEGF levels were below detectable limits in all plasma samples of all volunteers who participated in this study.…”
Section: Measurement Of Human Egf 55supporting
confidence: 70%
“…This activity was strongly affected by the dominant negative form of JNK and only minimally affected by the ERK1,2 pathway [Benasciutti et al, 2004]. In addition, studies on human keratinocytes have shown that estradiol‐dependent wound re‐epithelialization depends directly on HB‐EGF transcription enhancement which in turn, also depends on AP‐1 and Sp1 [Kanda and Watanabe, 2005]. These data strongly suggest that in our system uPA and HB‐EGF could share a similar transcriptional mechanism with JNK playing a central role.…”
Section: Discussionmentioning
confidence: 99%
“…Antisense oligonucleotides against NF-B p50 and p65, STAT1, c-Jun and c-Fos, and control scrambled oligonucleotides were synthesized by phosphoroamidite chemistry as described previously (19,22). Keratinocytes were transfected with the indicated oligonucleotides (0.2 M each) premixed with Fugene 6 in KGM for 6 h. The concentration of antisense oligonucleotides (0.2 M) was selected because this concentration did not reduce the viability of keratinocytes (Ͼ94% viable) and selectively reduced the levels of respective proteins in our previous study (22). The cells were treated with high-calcium KBM for 48 h and then incubated with 1 M histamine and/or 10 ng/ml IFN-␥ or TNF-␣.…”
Section: Methodsmentioning
confidence: 99%